Physical exercise: a therapeutic window for older adults with mild cognitive impairment (Revista científica Olimpia, 2025)
The magnitude and speed of demographic changes that are occurring in the world are very notable. Developing countries will be the protagonists of this aging process. Aging causes a functional deterioration in the elderly, with a decrease in their physical, cognitive and functional capacities, depending on each individual and their ability to adapt. Mild cognitive impairment is considered an intermediate stage between normal cognitive aging and dementia. The objective of the work is to review the relationship between population aging, taking into account the elderly, cognitive impairment and physical exercise today. In the review carried out, the importance of early diagnosis of elderly people with mild cognitive impairment using existing tools is a reality and not a myth. Starting with the appropriate treatment, mainly non-pharmacological, including physical exercise, improves cognition and daily life activities.
Keywords: elderly; memory disorders; mild cognitive impairment; physical exercises; functional impairment.